Flower color preferences of insects and livestock: effects on Gentiana lutea reproductive success - Sobral, Mar (PeerJ, 2016)
Angiosperms diversification was primarily driven by pollinator agents, but non-pollinator agents also promoted floral evolution. Gentiana lutea shows pollinator driven flower color variation in NW Spain. We test whether insect herbivores and livestock, which frequently feed in G.lutea, play a role in G. lutea flower color variation, by answering the following questions: (i) Do insect herbivores and grazing livestock show flower color preferences when feeding on G. lutea? (ii) Do mutualists (pollinators) and antagonists (seed predators, insect herbivores and livestock) jointly affect G. lutea reproductive success? Insect herbivores fed more often on yellow flowering individuals but they did not affect seed production, whereas livestock affected seed production but did not show clear color preferences. Our data indicate that flower color variation of G. lutea is not affected by insect herbivores or grazing livestock.